2005
DOI: 10.1557/proc-864-e7.3
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles and Cavities Induced by Rare Gas Implantation in Silicon Oxide

Abstract: In this pioneering study, we have extended noble-gas implant-induced cavity generation in Si and other semiconductors to a dielectric, viz., SiO 2 by implanting a variety of inert gas species. It has been seen that helium and neon do not induce bubbles/cavities in SiO 2 , regardless of implantation parameters and nature of the sample. Krypton and xenon implantation however result in bubbles/cavities formation in the oxide layer. In the case of Xe a minimum threshold dose of about 10 16 cm -2 is needed for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Indeed, we do not observe H-formed cavities in SiO 2 following implantation or annealing under a range of conditions ͑not shown͒. This is consistent with the results reported in the study of inert gas implantation in SiO 2 , 18 where the formation of implantationinduced cavities is only observed when heavy noble gas species such as Kr and Xe are implanted. Ntsoenzok et al also demonstrated that He or Ne implantation-induced cavities cannot be formed within SiO 2 , regardless of implantation temperature and attributed the lack of cavities to the high mobility of the gas atoms in SiO 2 .…”
Section: Methodssupporting
confidence: 92%
“…Indeed, we do not observe H-formed cavities in SiO 2 following implantation or annealing under a range of conditions ͑not shown͒. This is consistent with the results reported in the study of inert gas implantation in SiO 2 , 18 where the formation of implantationinduced cavities is only observed when heavy noble gas species such as Kr and Xe are implanted. Ntsoenzok et al also demonstrated that He or Ne implantation-induced cavities cannot be formed within SiO 2 , regardless of implantation temperature and attributed the lack of cavities to the high mobility of the gas atoms in SiO 2 .…”
Section: Methodssupporting
confidence: 92%
“…It should be noted that the accumulation of implanted noble gas ions leading to their clustering in the subsurface layers of irradiated materials was observed experimentally . The appearance of He and Ar clusters in silicon and silicon dioxide was confirmed for higher ion energies (>~1 keV) in contrast to the implantation of low‐energy ions, which can be thermally desorbed from the uppermost layers of the material because of the small implantation depth.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 82%
“…[ 28,29 ] It was also demonstrated that cavities in Si (formed by noble gas implantation) could act in gettering detrimental metallic impurities during wafer growth or subsequent processing for Si devices, [ 30–32 ] avoiding electronic properties degradation. [ 33,34 ] On the other hand, the xenon insertion can, in its turn, produce condensates as bubble‐like structures in Si [ 35 ] and SiO 2 [ 36–38 ] matrices or micro‐crystalline precipitates in metallic materials with FCC, BCC, and HCP structures. [ 39–42 ]…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] It was also demonstrated that cavities in Si (formed by noble gas implantation) could act in gettering detrimental metallic impurities during wafer growth or subsequent processing for Si devices, [30][31][32] avoiding electronic properties degradation. [33,34] On the other hand, the xenon insertion can, in its turn, produce condensates as bubble-like structures in Si [35] and SiO 2 [36][37][38] matrices or micro-crystalline precipitates in metallic materials with FCC, BCC, and HCP structures. [39][40][41][42] Given the relevance of the theme, the xenon nanobubbles formation and the residual damages in Xe + -implanted Si(001) substrate and its evolution under thermal annealing were investigated and discussed here.…”
Section: Introductionmentioning
confidence: 99%